Nanomechanical properties, wear resistance and in-vitro characterization of Ta2O5 nanotubes coating on biomedical grade Ti–6Al–4V. (February 2017) - Sarraf, Masoud; Razak, Bushroa Abdul; Nasiri-Tabrizi, Bahman; Dabbagh, Ali; Kasim, Noor Hayaty Abu; Basirun, Wan Jefrey; Bin Sulaiman, Eshamsul
Abstract: Tantalum pentoxide nanotubes (Ta2 O5 NTs) can dramatically raise the biological functions of different kinds of cells, thus have promising applications in biomedical fields. In this study, Ta2 O5 NTs were prepared on biomedical grade Ti–6Al–4V alloy (Ti64) via physical vapor deposition (PVD) and a successive two-step anodization in H2 SO4 : HF (99:1)+5% EG electrolyte at a constant potential of 15 V. To improve the adhesion of nanotubular array coating on Ti64, heat treatment was carried out at 450 °C for 1 h under atmospheric pressure with a heating/cooling rate of 1 °C min − 1 . The surface topography and composition of the nanostructured coatings were examined by atomic force microscopy (AFM) and X-ray electron spectroscopy (XPS), to gather information about the corrosion behavior, wear resistance and bioactivity in simulated body fluids (SBF). From the nanoindentation experiments, the Young's modulus and hardness of the 5 min anodized sample were ~ 135 and 6 GPa, but increased to ~ 160 and 7.5 GPa, respectively, after annealing at 450 °C. It was shown that the corrosion resistance of Ti64 plates with nanotubular surface modification was higher than that of the bare substrate, where the 450 °C annealed specimen revealed the highest corrosion protection efficiency (99%). Results from the SBF tests showed that a bone-like apatite layer was formed on nanotubular array coating, as early as the first day of immersion in simulated body fluid (SBF), indicating the importance of nanotubular configuration on the in-vitro bioactivity. Graphical abstract: Highlights: Ta2 O5 NTs were grown on biomedical grade Ti–6Al–4V alloy. Nanomechanical, wear and corrosion behavior were examined. H and E s of the 450 °C annealed sample were ~ 7.5 and 160 GPa. The 450 °C annealed coating showed the highest percentage of protection efficiency. A thick layer of bone-like apatite was formed after immersion in SBF for 14 days.